Mechanism of Gene Amplification via Yeast Autonomously Replicating Sequences - Shelly Sehgal; Sanjana Kaul; M. K. Dhar (The Scientific World Journal)
The present investigation was aimed at understanding the molecular mechanism of gene amplification. Interplay of fragile sites in promoting gene amplification was also elucidated. The amplification promoting sequences were chosen from the Saccharomyces cerevisiae ARS, 5S rRNA regions of Plantago ovata and P. lagopus, proposed sites of replication pausing at Ste20 gene locus of S. cerevisiae, and the bend DNA sequences within fragile site FRA11A in humans. The gene amplification assays showed that plasmid bearing APS from yeast and human beings led to enhanced protein concentration as compared to the wild type. Both the in silico and in vitro analyses were pointed out at the strong bending potential of these APS. In addition, high mitotic stability and presence of TTTT repeats and SAR amongst these sequences encourage gene amplification. Phylogenetic analysis of S. cerevisiae ARS was also conducted. The combinatorial power of different aspects of APS analyzed in the present investigation was harnessed to reach a consensus about the factors which stimulate gene expression, in presence of these sequences. It was concluded that the mechanism of gene amplification was that AT rich tracts present in fragile sites of yeast serve as binding sites for MAR/SAR and DNA unwinding elements. The DNA protein interactions necessary for ORC activation are facilitated by DNA bending. These specific bindings at ORC promote repeated rounds of DNA replication leading to gene amplification.